Coderivative necessary optimality conditions for sharp and robust efficiencies in vector optimization with variable ordering structure. (2nd July 2016) - Florea, Elena-Andreea
Abstract : In this paper, we define two new concepts of efficiency for vector optimization with variable ordering structure, namely the sharp and robust efficiencies, and we study their connections with classical concepts of efficiency in vector optimization. Then, we get necessary optimality conditions for them using Fréchet and Mordukhovich calculus coupled with the Gerstewitz's (Tammer's) scalarizing functional and openness results for set-valued maps.